2020
DOI: 10.1055/s-0039-3402758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking Cessation on the Pharmacokinetics and Pharmacodynamics of Clopidogrel after PCI: The Smoking Cessation Paradox Study

Abstract: Background Cigarette smoking is associated with enhanced clopidogrel effect and platelet inhibition. However, the effect of smoking cessation on clopidogrel pharmacokinetics (PK) and pharmacodynamics (PD) is unknown. We aimed to determine the effect of smoking cessation, confirmed by cotinine measurement, on clopidogrel PK and PD after percutaneous coronary intervention (PCI). Methods and Results Following successful PCI, patients treated with 75 mg/day clopidogrel who reported smoking ≥10 cigarettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
0
17
2
3
Order By: Relevance
“…Smoking has strong prothrombotic effects which may reduce the efficacy of anti-thrombotic drugs, requiring more sustained use of anticoagulant drugs in patients after coronary revascularization or with severe CHD in general. Conversely, smoking enhances the conversion of clopidogrel to its active metabolite, enhancing the anti-platelet effect of this drug [19,61]. Because of the prothrombotic effects of smoking, the risk of myocardial infarction and stroke is higher in women taking estrogen-containing oral contraceptives.…”
Section: Drug Interactions and Smokingmentioning
confidence: 99%
“…Smoking has strong prothrombotic effects which may reduce the efficacy of anti-thrombotic drugs, requiring more sustained use of anticoagulant drugs in patients after coronary revascularization or with severe CHD in general. Conversely, smoking enhances the conversion of clopidogrel to its active metabolite, enhancing the anti-platelet effect of this drug [19,61]. Because of the prothrombotic effects of smoking, the risk of myocardial infarction and stroke is higher in women taking estrogen-containing oral contraceptives.…”
Section: Drug Interactions and Smokingmentioning
confidence: 99%
“…The role of smoking on clopidogrel activity remains controversial. Some studies have concluded current smokers may have a higher clopidogrel metabolite exposure and pharmacodynamic effects than non-smokers (30), while cessation of smoking in clopidogrel-treated patients after PCI increased both VerifyNow P2Y12 platelet reaction units (PRUs) and platelet activity (31,32). Another study postulated the lower PRUs were due to higher hemoglobin levels in current smokers than non-smokers, and there was no difference of PRUs after adjustment for hemoglobin (33).…”
Section: Discussionmentioning
confidence: 99%
“…В исследовании B. Ramotowski et al прекращение курения, зафиксированное у пациентов европеоидной расы с помощью определения уровня котинина в моче системой Accutest NicAlert, было ассоциировано с повышением реактивности тромбоцитов на фоне лечения клопидогрелом [40]. В этом и других исследованиях функция тромбоцитов оценивалась с помощью основанной на принципе оптической трансмиссии тест-системы VerifyNow P2Y12, в которой в качестве активаторов агрегации используются аденозиндифосфат (АДФ) и простагландин Е1.…”
Section: Wwwjscientiaorgunclassified
“…Также наблюдалась взаимосвязь между эффектом отказа от курения и носительством аллелей, приводящих к потере функции: носители мутаций, ассоциированных с потерей функции (CYP2C19*2), бросившие курить, имели более высокий уровень реактивности тромбоцитов на фоне приёма клопидогрела, в то время как носители аллели дикого типа, продолжавшие курить, являлись подгруппой с наиболее низкой остаточной активностью тромбоцитов [40]. K. W. Park et al оценили функцию тромбоцитов у 810 пациентов из Кореи, получавших клопидогрел.…”
Section: Wwwjscientiaorgunclassified
See 1 more Smart Citation